TINJAUAN DIGITAL COLLABORATION NETWORK PADA START-UP DIGITAL DI PROVINSI JAWA BARAT: SEBUAH PENDEKATAN TRIPLE HELIX - Sukmadewi, Rani; Purbasari, Ratih; Kostini, Nenden (Adbispreneur, 2023)
The digital era has triggered a new technological revolution, affect significant structural changes in the industry, and ushered in the era of start-up businesses. Start-ups encounter a number of challenges, including the demand for greater digital capabilities, a weak supporting ecosystem, and difficulty accessing funding. This study aims to use a start-up relationship pattern approach with universities and the government to get an overview of the current situation and digital collaboration models for start-ups in West Java. Based on the co-inform dimension, digital start-ups in West Java have formed partnerships with other industry players and government. Only a few start-ups have undergone education and training efforts in co-learn settings. According to the co-market dimension, collaborative efforts between digital start-ups and other players in the digital innovation ecosystem have been made to promote goods or services at start-ups in West Java. Co-operation, co-produce, and co-build have yet to run optimally. The government, academics, and start-up actors have collaborated through digital collaboration networks at Digital Start-ups in West Java. However, this effort unsuccessful yet. Because each program's sustainability process could be improved, planning is necessary to create an organised, integrated, directed, and sustainable activity programme.Era digital telah memicu revolusi teknologi baru, menyebabkan perubahan struktural yang signifikan dalam industri, dan mengantarkan era start-up. Start-up memiliki berbagai kesulitan, termasuk kebutuhan akan keterampilan digital yang lebih banyak, ekosistem pendukung yang lemah, dan kesulitan mengakses pendanaan. Penelitian ini bertujuan untuk menggunakan pendekatan pola hubungan start-up dengan perguruan tinggi dan pemerintah untuk mendapatkan gambaran tentang keadaan saat ini dan model kolaborasi digital untuk start-up di Jawa Barat. Berdasarkan dimensi co-inform, start-up digital di Jawa Barat telah menjalin kemitraan dengan pelaku industri lainnya dan dengan lembaga resmi seperti organisasi pemerintah. Hanya beberapa start-up yang telah mengikuti upaya pendidikan dan pelatihan dalam pengaturan co-learn. Menurut dimensi co-market, upaya kolaborasi antara start-up digital dan pemain lain dalam ekosistem inovasi digital sudah dilakukan untuk mempromosikan barang atau jasa pada start-up di Jawa Barat. Co-operation, co-produce, dan co-build belum berjalan optimal. Pemerintah, akademisi, dan pelaku start-up telah berkolaborasi melalui digital collaboration network pada Digital Start-ups di Jawa Barat. Namun, upaya ini masih belum berhasil. Perencanaan diperlukan untuk menyusun program kegiatan yang terorganisir, terpadu, terarah, dan berkelanjutan karena proses keberlanjutan setiap program masih perlu ditingkatkan.